2009
DOI: 10.1007/s12403-009-0019-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Fecal Indicator Bacteria Densities in Marine Recreational Waters by QPCR

Abstract: The US EPA is currently investigating the use of quantitative PCR (qPCR) analysis techniques to estimate densities of fecal indicator bacteria (FIB) in recreational waters. Present water quality guidelines, based on culturable FIB, prevent same day water quality determination, whereas results from qPCR-based approaches are available within several hours. Epidemiological studies at Publicly-Owned Treatment Works (POTW)-impacted freshwater beaches have also indicated correlations between qPCR determined Enteroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 45 publications
2
50
0
1
Order By: Relevance
“…DNA standards for all qPCR assays were prepared from bacterial cultures as previously described (4,13,28). Cells were lysed in a bead mill for 60 s at maximum speed, and the debris was removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA standards for all qPCR assays were prepared from bacterial cultures as previously described (4,13,28). Cells were lysed in a bead mill for 60 s at maximum speed, and the debris was removed by centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…The four real-time PCR (qPCR) assays used in this study were Entero1, uidA, Cperf, and GenBac3 (4,7,20,28,35), for enterococci, E. coli, Clostridium spp., and Bacteroidales, respectively. The primer, TaqMan probe, and presumptive target organism(s) for each qPCR assay are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In order to select a Q-PCR assay and subsequently design RT-Q-PCR assays for E. coli with the highest levels of specificity, sensitivity, and efficiency, a literature review identified three frequently used functional genes for E. coli, uidA (24), tuf (25), and rodA (26) for comparison. The uidA gene (coding for ␤-D-glucuronidase) was chosen as the most frequently used target gene for E. coli (24,38,39,40,41).…”
Section: Test Panel Specificity and (Rt-)q-pcr Assaysmentioning
confidence: 99%
“…Water quality failures due to the survival or regrowth of E. coli within a WDS bring into question the suitability of E. coli as an indicator organism of fecal contamination. To achieve this, we first evaluated a number of current gene targets (24,25,26,27) and Q-PCR assays for E. coli. Furthermore, we expand their use by developing corresponding reverse transcription-quantitative PCR (RT-Q-PCR) assays to detect mRNA and explore their use as indicators of viable organisms.…”
mentioning
confidence: 99%
“…Of 20 µL of each DNA solution, 5 µL was used for real-time quantitative PCR. We used the primers (PCR product size, 130 bp) designed for the single-copy gene uidA to detect chromosomal DNA (Chern et al, 2009). In addition, we designed primers (5′-CCACATCGAGGAAGAAAACG-3′ and 5′-CACGAT-AGAGCACCCGGTAT-3′; PCR product size, 91 bp) for repA and primers (5′-AATGCCATGTGGTCAAAGGT-3′ and 5′-CGATGCAGTCCTGTATGTGC-3′; PCR product size, 99 bp) for repC by using Primer3 (http://bioinfo.ut.ee/ primer3-0.4.0/) and used them to detect the plasmid pHRP311.…”
Section: Fig 2 Distribution Of Delta Cq Valuesmentioning
confidence: 99%